An Analysis of Conversational Turn-Taking Strategies in the WSJ News Meeting Between Trump and Zelensky 2022 - Firdausy Alya Hasana; Suhartawan Budianto (Menulis: Jurnal Penelitian Nusantara, 2026)
This study analyzes conversational turn-taking strategies used in the WSJ News interview between Donald Trump and Volodymyr Zelensky. The aims of this study are to identify the types of turn-taking strategies used in the interview and to explain how these strategies organize the flow of conversation during a tense political interview. This research is based on Conversation Analysis, especially the turn-taking theory proposed by Anna-Brita Stenström (1994), which focuses on how speakers take turns, hold turns, interrupt, overlap, and repair speech in spoken interaction. A descriptive qualitative method is used, and the data are taken from a WSJ News video recording of the Trump–Zelensky interview. The spoken data are analyzed by identifying and classifying turn-taking strategies such as interruption, overlap, self-selection, turn-holding, and repair, and the findings are presented in tables to make the results easier to understand. The results show that several types of turn-taking strategies appear frequently, with interruption and overlap being the most dominant, especially during moments of disagreement and tension. The speakers often take turns competitively, which causes interruptions and overlapping speech, showing that turn-taking rules are not always followed. Overall, the findings indicate that turn-taking strategies play an important role not only in managing speaking turns but also in showing power, disagreement, and control in political media discourse.